2009
DOI: 10.1093/tropej/fmp030
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pneumonia in Mozambican Young Children: Clinical and Radiological Characteristics and Risk Factors

Abstract: Treatment of admitted children with severe pneumonia is complicated in settings with prevalent HIV and malaria. Children with severe pneumonia and clinical malaria require antibiotic and antimalarial treatment. In addition to vertical programs, integrated approaches may greatly contribute to reduction of pneumonia-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 32 publications
1
78
0
2
Order By: Relevance
“…HIV has been established as a strong risk factor for pneumonia and IPD [2,29]. Recent data from the same hospital show a 26% prevalence of HIV infection among children under 2 years of age admitted to hospital between March 2005-2006 with severe pneumonia [30]. Taking into account that S. pneumoniae is the leading cause of severe pneumonia in children, we can assume that the prevalence of HIV infection among cases included in our study would be remarkable.…”
Section: Paediatric Respiratory Infections X Vallès Et Almentioning
confidence: 74%
“…HIV has been established as a strong risk factor for pneumonia and IPD [2,29]. Recent data from the same hospital show a 26% prevalence of HIV infection among children under 2 years of age admitted to hospital between March 2005-2006 with severe pneumonia [30]. Taking into account that S. pneumoniae is the leading cause of severe pneumonia in children, we can assume that the prevalence of HIV infection among cases included in our study would be remarkable.…”
Section: Paediatric Respiratory Infections X Vallès Et Almentioning
confidence: 74%
“…22 Severe pneumonia accounted for 16% of hospitalizations among children less than two years of age, and had an associated case-fatality rate (CFR) of 11%. 23 Verbal autopsy studies confirmed from the community perspective that these two conditions are the leading causes of death in children less than five years of age. …”
mentioning
confidence: 89%
“…Treatment of malaria or severe pneumonia was conducted according to national guidelines, and has been described. 23,26 Antibiotic therapy was reassessed according to culture results and sensitivity patterns. Children requiring specialized care were transferred to Maputo Central Hospital.…”
mentioning
confidence: 99%
“…Para avaliar os fatores associados à pneumonia severa entre crianças menores de dois anos internadas em Moçambique, na África, Sigaúque et al (2009) conduziram um estudo transversal que identificou a anemia (OR=10,13), a desnutrição (OR=2,42) e a co-infecção com HIV (OR=17,21) como fatores de risco para a morte pela doença. A desnutrição e a anemia severas, associadas com a pneumonia grave, também estariam associadas à infecção pelo HIV.…”
Section: Ira Em Crianças Menores De Cinco Anos De Idade Aunclassified
“…Os benefícios do aleitamento materno para as crianças têm sido relacionados às menores taxas de diarreia, infecções do trato respiratório, otite média e outras infecções, e menor mortalidade por essas doenças em crianças amamentadas quando comparadas às não amamentadas (LEÓN-CAVA et al, 2002 Por fim, sem a pretensão de esgotar as possibilidades de atenção à criança na APS, destaca-se a importância do acompanhamento, controle e manejo de condições crônicas capazes de predispor a criança a um quadro grave de pneumonia, como as doenças de base pulmonar, as doenças cardiovasculares, as neuropatias graves, as doenças metabólicas e as imunológicas (JACKSON et al, 2013;NASCIMENTO-CARVALHO et al, 2002;RAMACHANDRAN, et al, 2012;SIGAÚQUE et al, 2009).…”
Section: Identificou Que Ounclassified